PROGRAM FOR ASSISTANCE AND EMPOWERMENT OF PKK ENERGY IN IMPROVING THE QUALITY OF BUSINESS ENTITIES OWNED IN SIDOKARE VILLAGE, REJOSO DISTRICT, NGANJUK REGENCY - Warjiyati, Sri; Salam, Safrin; Dita Wulandari, Mya (LPPM Univ. Ibn Khaldun Bogor, 2022)
The Sidokare Village-Owned Enterprise (BUMDes), which was founded in 2019, has succeeded in cooperating with village PKK women who are active members and operational in 2022. During the operation, the Sidokare BUMDes did not escape several obstacles. Through the PAR (Participatory Action Research) approach with the initial mapping stages, tansek, priority ranking, historical tracing, Venn diagrams, flowcharts, problem tree analysis, and hope tree analysis. So that the problem is obtained, namely, the failure of product marketing in BUMDes. This is due to the low knowledge of BUMDes executors, namely PKK women, in managing products in terms of quality and marketing. So that the product is not in demand by the village community. As a result of these problems, it is difficult to determine the selling price, it is difficult to attract buyers, the product manufacturing process is not optimal, and product marketing cannot be comprehensive in the community sector. This service program aims to help PKK women in improving the quality and marketing of soap products, as well as help the economy of the Sidokare BUMDes. The results of the training and mentoring program for PKK women in Sidokare Village are making BUMDes administrators and PKK women enthusiastic about producing and exploring activities to produce 100 dish soaps and 60 laundry soaps. The soap products are marketed to shops and the people of Sidokare. So that the product can be recognized and purchased easily by the people of Sidokare.